Laporan Akhir Kegiatan Magang di Badan Pengelola Pajak dan Retribusi Daerah Kota Palangka Raya Bagian Umum Kepegawaian - Husnul Khotimah; Haidi Hajar Widagdo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This report discusses a four-month independent internship experience at the Regional Tax and Retribution Management Agency of Palangka Raya City, specifically in the general staffing section. The internship aimed to connect theoretical knowledge gained in college with practical work experience in a government environment, as well as to develop administrative, communication, and teamwork skills. During the internship, the author was involved in various staffing administrative activities, such as recording and disposition of incoming and outgoing mail, managing employee data, and supporting internal operations. Through observation, interviews, and documentation methods, the author gained a deep understanding of staffing administrative procedures and the importance of accuracy and coordination in supporting smooth organizational operations. This experience also strengthened professional readiness and broadened insight into the work dynamics within government institutions. The implications of this activity demonstrate that systematic and professional staffing administration plays a crucial role in supporting organizational performance and achieving institutional goals